Antennas for Satellite Communication - Yadav, Viplav; Sandeep; Sharma, Sanjay (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2014)
Satellite communication antenna in unvield .It also comprises of transmitting/ receiving signal section and transmission of signal to satellite . it consist of various types of antennas used in satellite communication such as UHF, L/s band ,c-band, ku-band , k-band antennas. Multibeam broadband antenna and antennas for geostationary for satellite communication is also explained in this paper . This paper mainly describes the the signal transmitting/receiving antennas for satellite communication .